ANALISIS KEBIJAKAN OPTIMALISASI HAK PEMELIHARAAN DAN PENANGKAPAN IKAN DI WILAYAH PESISIR KOTA SEMARANG - Itsnani Mardlotillah; Susi Sulandari; Slamet Santoso (Journal of Public Policy and Management Review, 2013)
The research is included on qualitative research. Character of the writing processin this research is descriptive narrative. One of the reason background and reasoning blowup the issues is there no enough space for public interest in the coastal area policy inSemarang City. In cases, fisherman in Semarang has doesn’t freedom to run their dailyactivity to full fill their family needs. In other side, corporate is dominated investment onthat area, make any narrow space for public interest.The model consists of Problem Understanding, Aim Deciding, AlternativeFormulating, Modeling, standard Deciding, Alternative Development, Recommending, andBranding New Policy. In the research, researcher finds phenomenon going on the societywhich should be analyzed carefully. In cases unbalances government policy making. Thereno enough space for public interest to fill the policy. Then research focused in the classifiedproblem to formulate new branding policy which suitable with costal area society as anobject of the policy.